Upaya Radio El-Dity Meningkatkan Kualitas Siaran Menghadapi Persaingan Media Massa - Kurniawan; Edy Kusnadi; Ardiyansyah (MAUIZOH: Jurnal Ilmu Dakwah dan Komunikasi, 2020)
This research is motivated by the rapid development of online media. Radio strives for its broadcasts to continue to be of interest to listeners. The aim of the research is to see El-Dity radio's efforts to improve broadcast quality in the face of mass media competition. The research method is qualitative with data collection of observations, interviews, and documentation. Observations were made at the El-Dity radio studio, while the interview informants were the director and broadcaster of the bulletin program, the person in charge of reporting, and the broadcasters of El-Dity radio. The results of the study found that El-Dity radio had tried to improve the quality of bulletin broadcasts in order to face mass media competition, by selecting news that was interesting, broadcast worthy, up to date, and packaged in an attractive manner. Broadcasters try to present the news clearly, and another thing that El-Dity radio does to improve the quality of its bulletin broadcasts is to divide its broadcast segmentation with various types of regional, national and international news.